Schemes of multi-parameter stations in the Bering and Chukchi Seas and North Pacific made in research cruises of TINRO (1986–2019) - A. F. Volkov (Известия ТИНРО, 2020)
Spatial distribution of stations made in research expeditions conducted by Pacific Res. Inst. of Fisheries and Oceanography (TINRO) in the Bering and Chukchi Seas and in the North Pacific in 1986–2019 is discussed. Schemes of the stations for every cruise are presented and sorted by decades, years, seasons, and months. The data sufficiency is estimated at regional and temporal levels by calculation of the stations number in the daytime and nighttime, per years, per seasons, and per biostatistical areas.